PREDIKSI DEBIT SUNGAI BENGAWAN SOLO MENGGUNAKAN NUMERICAL WEATHER MODEL GLOBAL FORECAST SYSTEM DAN INTEGRATED FLOOD ANALYSIS SYSTEM (Prediction of discharge in Bengawan Solo River using Numerical Weather Model Global Forecast System and Integrated Flood Analysis System) - Deffi Munadiyat Putri; Aries Kristianto (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2021)
ABSTRACT Flood is one of the most common hydro-meteorological disasters. Bengawan Solo is one of thewatersheds in Indonesia that also hit by this disaster. This study discusses the flood disaster inthe Bengawan Solo area in early March 2019. The purpose of this study is to conduct adischarge simulation using numerical weather model Global Forecast System (GFS) datathrough Integrated Flood Analysis System (IFAS) so it is possible to predict discharge in thefuture. There are three types of numerical weather model GFS data that have been downscaleusing weather research and forecasting model which differentiated based on spin-up time. Thenumerical weather model product is then used as rainfall data input for IFAS simulation. Basedon the analysis, the flood discharge simulation using an 84-hour spin-up time has a satisfactoryperformance in describing the change in discharge with respect to time. This happens because numerical weather models will be better at quantifying processes that occur on a meso scalewith spatial scale of 10 to 1000 km. The result of this research shows that it is possible to predict river discharge up to 84 hours before the disaster so this is can support the mitigationprocess for hydrometeorological disasters. Keyword: Global Forecast System; Flood Analysis System; spin-up ABSTRAKBanjir merupakan salah satu bencana hidrometeorologi yang sering terjadi. Bengawan Soloadalah salah satu DAS di Indonesia yang juga dilanda bencana ini. Kajian ini mendiskusikanbencana banjir di kawasan Sungai Bengawan Solo pada awal Maret 2019. Tujuan daripenelitian ini adalah untuk melakukan simulasi debit dengan menggunakan model cuacanumerik Global Forecast System (GFS) melalui Integrated Flood Analysis System (IFAS)sehingga dimungkinkan untuk adanya kegiatan prediksi debit yang lebih akurat, cepat dantepat pada periode waktu tertentu. Terdapat tiga jenis model cuaca numerik GFS yang telah didownscale menggunakan model Weather Research and Forecasting (WRF) yang dibedakan berdasarkan waktu spin-up. Produk model cuaca numerik tersebut kemudian dijadikan data masukan hujan untuk simulasi IFAS. Berdasarkan analisis diketahui bahwa simulasi debit banjir menggunakan waktu spin-up 84 jam memiliki performa memuaskan dalam menggambarkan perubahan debit terhadap waktu. Hal ini terjadi karena model cuaca numerik akan semakin baik dalam mengkuantifikasi proses yang terjadi dalam skala meso dengan resolusi spasial 10 hingga 1000 km. Hasil penelitian ini menunjukan bahwa memungkinkan untuk melakukan prediksi debit sungai hingga 84 jam sebelum bencana sehingga hal ini sangat mendukung dalam proses mitigasi becana hidrometorologi.Kata kunci: Global Forecast System; Flood Analysis System; spin-up